2021
DOI: 10.2967/jnumed.120.246819
|View full text |Cite
|
Sign up to set email alerts
|

Technologic (R)Evolution Leads to Detection of More Sentinel Nodes in Patients with Melanoma in the Head and Neck Region

Abstract: BackgroundSentinel lymph node (SN) biopsy (SLNB) has proven to be a valuable tool for staging melanoma patients.Since its introduction in the early 1990s, this procedure has undergone several technological refinements, including the introduction of single photon emission computed tomography combined with computed tomography (SPECT/CT) as well as radio-and fluorescence-guidance. The purpose of the current study was to evaluate the effect of this technological evolution on SLNB in the head and neck region. Prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Moreover, SPECT/CT is more expensive, requires extra time, and delivers an additional, yet low radiation dose [8,27,28]. It has been suggested that this method should only be used in patients with non-visualization of SLN on planar imaging, where drainage pattern is variable or unpredictable and when conventional imaging is difficult to interpret [8,29,30]; however, the introduction of improved SPECT/CT systems and advanced detection techniques have led to a higher number of identified SLNs and better surgical workflow, without increasing the overall operation time [31]. Nonetheless, dynamic PLS should not be abandoned, as it is the only method differentiating an additional SLN from a second-tier lymph node.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SPECT/CT is more expensive, requires extra time, and delivers an additional, yet low radiation dose [8,27,28]. It has been suggested that this method should only be used in patients with non-visualization of SLN on planar imaging, where drainage pattern is variable or unpredictable and when conventional imaging is difficult to interpret [8,29,30]; however, the introduction of improved SPECT/CT systems and advanced detection techniques have led to a higher number of identified SLNs and better surgical workflow, without increasing the overall operation time [31]. Nonetheless, dynamic PLS should not be abandoned, as it is the only method differentiating an additional SLN from a second-tier lymph node.…”
Section: Discussionmentioning
confidence: 99%
“…The use of fluorescence-guided SN biopsy is rising, but this field has benefited strongly from nuclear medicine; radiotracer-dye combinations for SN biopsy have existed since the 1990s with lymphoscintigraphy together with patent blue dye. Since then, refinements in technology and dyes (e.g., introduction of ICG) have increased SN biopsy efficiency, with greater numbers of SNs identified without increasing overall operation time (29).…”
Section: Sentinel Lymph Node Biopsymentioning
confidence: 99%
“…Image-guided applications play an important role in the current progression realized in the field of head-and-neck surgery [ 1 , 2 , 3 , 4 ]. A prime example of such an approach is found in the surgical resection of sentinel nodes, a procedure that serves as a secondary means for the identification of (micro)metastatic tumor spread [ 1 , 2 , 5 , 6 ]. An upcoming application is found in the visualization of primary tumor margins [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%